Distribution & Sales Control in Music Companies in the Industrial Era 4.0: A Case Study in the Indonesian Music Industry - Sulaiman Effendi; Edy Firmansyah (Budapest International Research and Critics University, 2022)
On April 4, 2018 the Government of the Republic of Indonesia through the Ministry of Industry & Trade launched the 'Making Indonesia 4.0' program as a road map towards industrial competitiveness and industrial transformation. In a step to implementing Making Indonesia 4.0, the Ministry of Industry & Trade of the Republic of Indonesia also launched the Indonesia Industry 4.0 Readiness Index (INDI 4.0). Namely the Index to measure the industry's readiness to transform and a reference to access the industry's readiness to transform itself. In Indonesia, the music industry has also developed towards 4.0, which is still intended for users of music products in Indonesia, namely Karaoke Companies. Namely a company in the tourism and entertainment industry that provides space services, musical instruments and catalogs of various songs. The problem is, the quantity of playback of each song A, B and or C still cannot be controlled properly by the Government, where and only hand over control to music publishers who have licenses and permits from the Government as an institution that controls the circulation of products and works of artists, as a result there is no clear transparency regarding reporting so that the control provided is not optimal. This results in an unequal distribution of profits, so that the profits obtained are still mostly owned by some collectors who are under the auspices of music publishers and often harm the creators of works, as well as musicians, so that they do not get the royalties or remuneration that they receive. and can also harm the Government, where the Government should derive income from taxes in the music industry. However, in reality the Government does not earn significant income from taxes in the music industry because the games from several music publishers tend to play a hidden role in generating profits in the music industry, so that the supporting infrastructure in the recording process and the process of monitoring the distribution and circulation of music products is still not yet available. exist, so that the necessary control is still weak, and provides opportunities for unequal distribution of results to creators, musicians and also the Government by Collectors due to the sale of all performance rights and mechanical rights through entertainment venues and channels.Digital Music Distribution (Music Aggregator) is not transparent and tends to harm the creators of works, musicians and also the Government regarding acceptance.